Estrategia pedagógica mediada por TIC para fortalecer la competencia de razonamiento matemático en estudiantes de sexto grado - Acosta-Guarnizo, Lina-María; Valdivieso-González, Luis-Gabriel; Muñoz-Potosi, Andrea-Fernanda (Revista Científica, 2023)
The aim of this research was to design a pedagogical strategy mediated by ICTs to strengthen the learning competencies associated with mathematical reasoning for problem solving in sixth grade (equivalent to junior high school) students at Centro Educativo Campo Galán, located in the Campo Galán Township of Barrancabermeja, Santander, Colombia. This project followed a quantitative approach, where a diagnostic test was designed in order to evaluate numerical, spatial-metric, and random thinking. The analysis of the results allowed determining the students’ level of mathematical reasoning. The flaws found were the basis upon which a virtual and playful pedagogical strategy was designed. This motivated and led to pleasant spaces for attractive and meaningful learning. The strategy was titled En el campo cuento y aprendo [Counting and learning in the field], and its main objective was to present a problem situation which would motivate and improve mathematical reasoning for problem solving. The results obtained evidenced a significant increase in the students’ performance regarding numerical and random thinking, as well as in spatial-metric thinking to a lesser extent.